Analysis of the relationship between children’s social media, smartphone and game addiction - Üstündağ, Alev (Journal of Dependence, 2022)
Objective: This research was conducted to determine whether there is a relationship between children’s social media addiction, smartphone addiction, and game addiction. Method: The research was carried out using the correlational method, one of the quantitative research methods. 248 children between the ages of 12-15 participated in the study. Data collection tools are Personal Information Form, The Smartphone Application-Based Addiction Scale, Bergen Social Media Addiction Scale and Internet Gaming Disorder Scale. Results: There is a relationship between children’s social media addiction levels and game addiction levels and smartphone addiction levels, and there is a significant and positive relationship between children’s game addiction levels and smartphone addiction levels (. In other words, there is a significant and positive relationship between the use of smartphones and the level of addiction to both social media and games. As a result of the analysis made according to the gender variable, there was a relationship between the social media addiction levels of the female students and the game addiction levels and the smartphone addiction levels, and there was a relationship between the game addiction levels and the smartphone addiction levels. On the other hand, there was a negative and weak relationship between social media addiction levels and game addiction levels of male students (r=-.292, p=.001), but there was a positive and moderate relationship between game addiction levels and smartphone addiction levels. Conclusion: In the digital age, it is not possible to keep children away from the screen. The results of the research show that all of the children use smartphones, play online games, use any social media application, and that there is a significant and positive relationship between smartphone use and both social media and game addiction levels. For this reason, support programs can be created to provide media literacy education to children in order to make the time spent in front of the screen more qualified and supportive of their development.